Implementasi Multi-Factor Authentication Untuk Optimalisasi Keamanan Akses Data Di PT.ABC - Haeruddin, Haeruddin; Prasetyo, Stefanus Eko; Mindy, Avista (Jurnal Manajemen Informatika JAMIKA, 2025)
This study explores the implementation of Multi-Factor Authentication (MFA) as a strategic measure to enhance data security at PT. ABC, where the company's online system previously relied solely on traditional authentication methods such as usernames and passwords. In the context of the rapid increase in internet users following the Covid-19 pandemic, data security has become a critical issue. Through observation, interviews, and the Network Development Life Cycle (NDLC) approach, this study identifies existing security vulnerabilities and proposes an MFA-based solution using the Auth0 service. The implementation was tested through system penetration using the Burp Suite tool to ensure resilience against cyber attacks. The results demonstrate that the implementation of MFA significantly improves protection against unauthorized access and increases security awareness among employees. This study highlights the importance of adopting advanced authentication technology as an integral part of a company's data security strategy to address increasingly complex cyber challenges.